Literature Review: Effectiveness of Management of School Operational Assistance Funds - Budi Mawan Aris; Muryani Arsal; Ismail Badollahi (Pustaka Digital Indonesia, 2026)
The management of School Operational Assistance (BOS) funds serves as a primary pillar in financing primary and secondary education in Indonesia. Although budget allocations continue to increase, management effectiveness still faces challenges regarding transparency, timeliness, and its impact on the quality of learning. Objective: Therefore, this study aims to examine the effectiveness of BOS fund management in schools through a systematic literature review. Methods: This research employs the Systematic Literature Review (SLR) method as a qualitative approach. Data were collected from various journals and articles published between 2020 and 2025. Findings: The findings indicate that the effectiveness of fund management is significantly influenced by the digitalization of reporting systems (such as ARKAS), the managerial competence of school principals, and the level of school autonomy. International literature emphasizes that financial effectiveness must ultimately lead to improved student achievement, whereas domestic literature still focuses heavily on administrative compliance. Conclusion: The primary constraints consistently identified include delays in fund disbursement and low community participation in oversight. Furthermore, regulatory changes and human resource limitations remain major challenges affecting the overall effectiveness of BOS fund management.